2022
DOI: 10.2196/30286
|View full text |Cite
|
Sign up to set email alerts
|

Implications and Preventions of Cyberbullying and Social Exclusion in Social Media: Systematic Review

Abstract: Background The growth of social networking has created a paradigm in which many forms of personal communication are being replaced by internet communication technologies, such as social media. This has led to social issues, such as cyberbullying. In response, researchers are investigating cyberbullying to determine its implications in various life sectors. Objective This manuscript reviews the methods, results, and limitations of the current cyberbullyi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Using social media as a health intervention or to distribute health interventions comes with multiple risks for adverse events. Becoming a victim of cyberbullying [9,10] or misinformation [11] could be some possible adverse events -but only a few studies report on them. On the other hand, studies on cyberbullying in social media are available [12] and misinformation also has been assessed by researchers.…”
Section: Resultsmentioning
confidence: 99%
“…Using social media as a health intervention or to distribute health interventions comes with multiple risks for adverse events. Becoming a victim of cyberbullying [9,10] or misinformation [11] could be some possible adverse events -but only a few studies report on them. On the other hand, studies on cyberbullying in social media are available [12] and misinformation also has been assessed by researchers.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of previous research (Ademiluyi et al, 2022;Alim, 2016;Boddy, Dominelli, 2017;Özel et al, 2017;Rajbhandari, Rana, 2022;Schodt et al, 2021;Singh et al, 2020) observed that negative social interactions in social media will be considered as a possible problem to lose social media users' face. In framing face-saving behavior, users must learn or develop an instrument as a personal assistant that is politeness strategies (Andriuzzi, Michel, 2021;Eshghinejad, Moini, 2016;Maros, Rosli, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…As per the use and gratification theory (UGT) of the cyber space (Suler, 1999), when faced with exclusive interaction with adults, teenagers might turn to social platforms for a sense of belonging and all types of relationships (David & Roberts, 2017). Previously, studies revealed that exclusive social behaviors could elevate people's social network usage rates (Büttner & Rudert, 2022), which may contribute to social media reliance (Ademiluyi, Li & Park, 2022).…”
Section: Parental Phubbing and Psnumentioning
confidence: 99%